(3GdHjWQIs ((3CMeO Hf YHOGdQMef s)
(3ChdgG (B:s
(3eHJhQ GdChd, hChd GdehLhO efg(B: (3QDhS GdPQGYjf YfO edJbi GdYVOjf, hPdc Cbhi djOjg, hLOJgeG CTO dhUhd GdPQGYjf aj GdYVOjf hWhd PQGYjg, hPQGYg eG Hjf YVOjg hQcHJjg, hZdXgeG hYHGdJgeG hYQVgeG s
(3BNQgG (B:s
(3hjSbi fMdkG MGObkG MJi jUjQ eQgekG, Ke jSJYed Ydi GdEfJTGQ hGdChQGe HEPf Gddg YR hLd, hdChQGe GdLha jSbj efg HTQGH(B: (3fGaY HEPf Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B42 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs